Klasifikasi Penyebaran Covid-19 Menggunakan Algoritma C4.5 Kota Pagar Alam - Rega Satya Putra; Erwin Dwika Putra; M. Husni Rifqo; Harry Witriyono (JUKOMIKA (Jurnal Ilmu Komputer dan Informatika), 2021)
Allof countriesinthe world,includingIndonesia faced the Covid-19 pandemicorthecoronavirusatthebeginning of2020.Thisvirus isknownthat firstappearedinHubeiProvince,WuhanCity,ChinaattheendofDecember 2019.The riskofCovid-19transmissioncanbe avoidedwithpublic discipline by reducingactivitiesinthemiddleofa crowdifthere isnoneedandimplementing healthprotocols.Thedevelopmentofinformationtechnology makeiteasierfor peopletoeasily obtaindatathattendstoberedundantandclassificationactivities thatcarriedout by humansstillhavelimitations,especially thehumanability to accommodatedata tobe classified.The amountof datathatentersaninstitutionor organizationevery day,thelongerthemoreitwillbe,thepileofdatawillbe accumulatedsothattheutilizationisnotoptimal.Thisstudy aimedtobuiltthethe classificationofcovid-19databy usingtheC4.5AlgorithminthecityofPagar AlamwiththeCRIPS-DMmethodwiththeX-crossvalidationopratorsmodel. TheresultsobtainedintestingbyapplyingtheC4.5algorithmtotheCovid-19 dataforthecity ofPagarAlamshowthattheaccuracyresultsare86.67%andthe AUC (Optimise) resultsare0.989.